Democracy, state capacity and the governance of COVID-19 in Asia-Oceania - Croissant, Aurel; Hellmann, Olli (Routledge, 2023)
Introduction : democracy and state capacity during times of crisis / Aurel Croissant & Olli Hellmann -- Policy responses to the COVID-19 pandemic : an aggregate level comparative analysis / Jale Tosun -- COVID-19 and democracy : creeping autocratization? / Aurel Croissant & Lars Pelke -- Closing the borders to COVID19 : democracy, politics and resilience in Australia and New Zealand / Jennifer Curtin & Dominic O'Sullivan -- Containing COVID-19 in South Korea and Taiwan : state capacity and geopolitics / Yin-wah Chu -- Navigating the early impacts of COVID-19 : South Pacific viewpoints from Fiji and Samoa / Audrey Aumua, Saunimaa Ma Fulu-Aiolupotea, Tamasailau Suaalii-Sauni & Tim Fadgen -- The pandemic and competitive authoritarianism in India / Rahul Mukherji and Seyed Hossein Zarhani -- Economy first : Indonesia's calculated underutilization of state capacities and democratic resources in the early phase of COVID-19 / Marcus Mietzner -- COVID-19 in the Philippines and Cambodia : rising autocracy and weak state capacity / Erik Martinez Kuhonta, Keovathanak Khim & Tynarath Huon -- Singapore and Hong Kong : the effect of trust in high-capacity hybrid regimes / Mathew Y.H. Wong & Adrian M.H. Lam -- Proactive responsiveness and institutionalization in Vietnam's offensive against COVID-19 / Nhu Truong -- China's response to the COVID-19 Pandemic. Navigating internal and external challenges / Heike Holbig.
Keywords: Asien; Ozeanien